Pengaruh Pemberian Honey Bee Pollen terhadap Nafsu Makan dan Berat Badan Siswa Sekolah Dasar - Nurkhalishah Malik; Citra Kesumasari Yaksan; Rosmini Rosmini (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the extent of the effect of honey bee pollen supplementation on increasing appetite and body weight in anemic children. The type of research used in this study is an experimental study with a pre- and post-test one-group design. The research sample consisted of 52 anemic fourth- and fifth-grade elementary school students. The average total food intake (Yellow Rice) showed a significant result (P=0.000), increasing from 241.40±94.334 g to 354.94±122.57 g after the final measurement of ad libitum appetite. The average body weight also showed a significant result (P=0.00), with a mean of 23.59±5.29 kg at pre-test and rising to 24.65±5.58 kg at post-test. The Z-Score calculation for weight-for-age based on the WHO NCHS reference showed a non-significant result: P=0.0180 (0.01±0.04) at pre-test and 0.03±0.08 at post-test. Based on the 24-hour recall analysis over two days, a significant result was obtained (P=0.000), with total energy intake of elementary school students increasing from an average of 1,594±420.17 kcal before intervention to 2,070.2±491.77 kcal after two months of intervention. After statistical testing (Paired T-Test), a P-value of 0.00 (<0.05) was obtained. It can be concluded that the administration of honey bee pollen for 8 weeks at a dose of 25 grams per day significantly increased appetite and body weight in anemic elementary school children.